Surgical Guide for Restorative Orthognathic Procedure - Pizoni, Elisabeth; Barbeiro, Roberto Henrique; Barbeiro, Camila de Oliveira; Iqbal, Muhammad Naeem (PSM Biological Research, 2023)
Dental models have been helping surgeons to preview accurately what they must accomplish during surgery. Although a patient-specific model gives the surgeon the ability to plan and feel what they will be dealing with during the surgery, it would give a lot of worries and work very hard work to make a perfect model that could give a true image of the problems that could be faced during the procedure. This is where 3D printing technology comes in, 3d printing can decrease the number of surprises that could occur during the procedure. The benefits of 3D printing are to give the surgeon the skill to see patient-specific anatomical models, rather than viewing X-rays, ultrasound images, computed tomography (CT) images, or magnetic resonance imaging (MRI) images that might not be as clear as the surgeon would like. This skill can lead the surgeon greater insight as to what he/she will be facing during the procedure and give a more satisfactory outcome for the patient. When things don't go well in surgery, the operation’s time and costs increase, and the patient’s recovery time might be extended with many other expenses. The best the surgeon knows the patient’s anatomy the best he/she can overcome some unexpected situations during the surgery. The aim of this article is to report a prognathic reparative surgery using a 3d surgical guide to plan the steps of it as well as the best way to follow them.